El tractament de la -n > N' en català - Gulsoy, Joseph (Caplletra. Revista Internacional de Filologia, 1996)
In this article, the author studies the eliminating process of -n < N' in Catalan, process that, in accordance with the documentation that he contributes, it reveals partially during 10th century and it looks to be consummated at the end of 1 lth century —excepting Rosellonese language— in singular forms, whereas in -ns plural forms, the -n was preserved. He also analyses the differences among this solution, Gascon language and Spanish dialects.